2020
DOI: 10.1089/wound.2019.1091
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Model to Predict Healing of Chronic Wounds Within 12 Weeks

Abstract: Pré cis: Using both clinically informed and machine learning approaches, we developed a prediction model for chronic wound healing that can form the basis for quality measurement. Objective: Chronic wounds represent a highly prevalent but little recognized condition with substantial implications for patients and payers. While better wound care products and treatment modalities are known to improve healing rates, they are inconsistently used in real-world practice. Predicting healing rates of chronic wounds and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 36 publications
1
50
1
Order By: Relevance
“…Quantitative tissue cultures of wound biopsies are the reference standard to quantify bacterial load, but prolonged turnaround time between biopsy and microbiological results limits the rapid decision making needed to effectively manage bacterial burden in wounds. The relative inconsistency of CSS and delays in results from microbiological culture and PCR analysis may explain why 12-week wound healing rates are below 60% 7 and have remained stagnant over the past 40 years, 20 despite tremendous advances in wound treatments.…”
Section: Clinical Problem Addressedmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative tissue cultures of wound biopsies are the reference standard to quantify bacterial load, but prolonged turnaround time between biopsy and microbiological results limits the rapid decision making needed to effectively manage bacterial burden in wounds. The relative inconsistency of CSS and delays in results from microbiological culture and PCR analysis may explain why 12-week wound healing rates are below 60% 7 and have remained stagnant over the past 40 years, 20 despite tremendous advances in wound treatments.…”
Section: Clinical Problem Addressedmentioning
confidence: 99%
“…It is known that increased microbial load is a key predictor of nonhealing wounds. 7,8 Proliferation of bacteria resulting in moderate-to-heavy loads (>10 4 colony-forming units [CFU]/g) delays healing [9][10][11] and increases the risk of wound complications, including infection, sepsis, and amputation. [12][13][14] Guidelines advise that early diagnosis of high bacterial burden is essential to prevent the wound from progression to local or systemic infection.…”
Section: Introductionmentioning
confidence: 99%
“…A recent article evaluating the medical records of over 100,000 patients reported that only 14.9% of pressure ulcers healed by 12 weeks. 2 A variety of local and systemic factors contribute to delayed wound healing in PUs, including age, wound size and depth, bacterial burden, elevated matrix metalloproteases, unrelieved pressure, and comorbidities such as diabetes, renal disease, malnutrition and obesity. [2][3][4][5] The most commonly used staging system for PUs (also known as pressure injuries), published by the National Pressure Injury Advisory Panel (NPIAP), designates full-thickness ulcers as Stage 3 or 4.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent publication looking at predictive models of wound healing confirmed that wound surface area was a significant factor in determining likelihood of healing. 10 In 2004, Margolis found that VLU duration (less than or greater than 1 year) and size (less than or greater than 10cm 2 ) were prognostic indicators of healing. 11 For example, the Margolis study predicted that the likelihood of healing a VLU >1 year duration and > 10 cm 2 in size was only 26%.…”
Section: Discussionmentioning
confidence: 99%
“…Their study considered VLU's that had been present on average for 17.9 weeks (SD 30.3 weeks) prior to treatment and also found smaller wounds healed faster 6 . A recent publication looking at predictive models of wound healing confirmed that wound surface area was a significant factor in determining likelihood of healing 10 …”
Section: Discussionmentioning
confidence: 99%